Neurobiological Functions of the Period Circadian Clock 2 Gene, Per2 - Mikyung Kim; June Bryan de la Peña; Jae Hoon Cheong; Hee Jin Kim (2017)
Most organisms have adapted to a circadian rhythm that follows a roughly 24-hour cycle, which is modulated by both internal (clock-related genes) and external (environment) factors.In such organisms, the central nervous system (CNS) is influenced by the circadian rhythm of individual cells.Furthermore, the period circadian clock 2 (Per2) gene is an important component of the circadian clock, which modulates the circadian rhythm.Per2 is mainly expressed in the suprachiasmatic nucleus (SCN) of the hypothalamus as well as other brain areas, including the midbrain and forebrain.This indicates that Per2 may affect various neurobiological activities such as sleeping, depression, and addiction.In this review, we focus on the neurobiological functions of Per2, which could help to better understand its roles in the CNS.